AB0379 Subclinical atherosclerosis in the femoral arteries: similar prevalence in rheumatoid arthritis and diabetes mellitus in a case control study. (23rd January 2014) - Protogerou, A.; Zampeli, E.; Tentolouris, N.; Makrilakis, K.; Kitas, G.D.; Sfikakis, P.P.
Abstract : Background: Rheumatoid arthritis (RA) is associated with increased coronary artery disease (CAD) and subclinical carotid atherosclerosis, both reported to equal diabetes mellitus (DM), a CAD equivalent. On the other hand, the presence of CAD in the general population has been strongly associated with subclinical atherosclerosis in the femoral arteries. Objectives: To compare the presence of atheromatic plaques in femoral arteries in RA versus DM patients. Methods: Femoral plaques were identified by ultrasonography in non-diabetic RA patients matched 1:1 for age, gender and disease duration with diabetic patients. All were asymptomatic and free of CAD. Results: Twenty-one middle aged (11 men, age: 41.9±11 years, disease duration: 10.6±7.4years) and 29 elderly RA patients (14 men, age: 62.8±7.9 years, disease duration: 10.5±7.6years) were matched with DM patients type 1 or 2, respectively. Prevalence of hypertension, dyslipidemia and obesity was higher in DM. The number of femoral plaques per subject was identical between RA and DM subjects (0.68±0.84 vs 0.68±0.87 respectively); numbers of patients with femoral plaque were also similar (middle-aged RA vs DM type 1: p=0.955; elderly RA vs DM type 2: p=0.559). As expected, elderly RA patients had more femoral plaques by 3-fold than middle-aged patients (p=0.034). Conclusions: Despite the higher burden of classical cardiovascular disease risk factors in DM, subclinical femoral atherosclerosis in RA is similar to DM of equal disease duration, further confirming the territorial unrestricted acceleration of the atheromatic process in these patients. The issue of cardiovascular risk stratification based on both carotid and femoral plaques detection in RA should be addressed prospectively. Disclosure of Interest: None Declared